Asymmetric impact of Atlantic Multidecadal Oscillation on El Nino and La Nina characteristics - Sung, MK; An, SI; Kim, BM; Kug, JS (Geophysical Research Letters, 2015)
The long-lasting cold surface conditions of North Atlantic, i.e., the negative phase of Atlantic Multidecadal Oscillation (AMO), can intensify the El Nino-Southern Oscillation through the enhanced air-sea coupling under the increased central-to-eastern tropical Pacific mean sea surface temperature. However, the impact of warmer mean sea surface temperature (SST) is more efficient in the intensifying El Nino than La Nina, because of the nature of the exponential growth of atmospheric convection to SST change. Moreover, the farther eastward shift of the atmospheric convection during the negative AMO leads to the stronger El Nino due to the longer delayed negative feedback by oceanic waves. Therefore, the AMO mainly influences the El Nino intensity rather than La Nina intensity. △ 1 1 2 2 Y scie scopus